Basic compounds for superalloys : mechanical properties - Pelleg, Joshua (Elsevier, 2018)
Basic Compounds for Superalloys: Mechanical Properties explores the mechanical properties of the iron group based intermetallic compounds that are the basis of super-alloys. Chapters explore tensile tests and compressive stress and hardness and provide detailed considerations that are devoted to time dependent deformation, namely creep and cyclic deformation. In addition, a discussion of the nano-crystalline L12 and B2 structures and their mechanical properties is included. Fracture and failure of these materials in both macro and nano-iron based compounds is also considered. This book is ideal for engineers, scientists and technical personnel who work in materials engineering, materials science, and mechanical and chemical engineering. Provides an in-depth focus on the mechanical properties of Fe- superalloy materialsIncludes a discussion of the static, time dependent and cyclic deformation properties of macro- and nano materialsReviews how superalloy materials behave under a variety of 'in-service' environments and conditions.